2010
DOI: 10.1007/s11581-010-0450-1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and electrical properties study of 4-aminopyridinium chloridobismuthate (III) (C5N2H7)4.HBi2Cl11

Abstract: The crystal structure of (C 5 N 2 H 7 ) 4 .HBi 2 Cl 11 has been determined at room temperature by single crystal X-ray diffraction. The compound crystallizes in the triclinic system with Pī space group. The crystal structure consists of two asymmetric inequivalent molecules of 4-aminopyridinium and anionic HBi 2 Cl 11 chains. The HBi 2 Cl 11 anionic chains stacked along the a-axis are formed with Bi 2 Cl 11 dimers connected to each other via hydrogen atoms. The crystal packing is stabilized with N-H...Cl hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…There are nointeractions in the structure of (I) in contrast to the closely packed complex [Cd(HOABDC)] n (Wang, Li, Yang & Zhao, 2012). Pyridine can be easily protonated with an inorganic acid (hydrochloric acid) or even an organic acid (5-hydroxyisophthalic acid) (Khelifi et al, 2010;Wheatley et al, 1999). As electron-donating groups, -NH 2 or -OH could improve the base strength of the pyridine ring.…”
Section: Figurementioning
confidence: 99%
“…There are nointeractions in the structure of (I) in contrast to the closely packed complex [Cd(HOABDC)] n (Wang, Li, Yang & Zhao, 2012). Pyridine can be easily protonated with an inorganic acid (hydrochloric acid) or even an organic acid (5-hydroxyisophthalic acid) (Khelifi et al, 2010;Wheatley et al, 1999). As electron-donating groups, -NH 2 or -OH could improve the base strength of the pyridine ring.…”
Section: Figurementioning
confidence: 99%
“…It's clear from this graph that the radius of the arcs decreases with the increase of temperature. So, the process of electrical conduction in the studied hybrid compound is thermally activated ).…”
Section: Resultsmentioning
confidence: 93%
“…So, the process of electrical conduction in the studied hybrid compound is thermally activated. [35] In order to study the electric properties, the impedance components are fitted using Zview software and the best fit is obtained when employing an equivalent circuit model which formed by a parallel combination the bulk resistance R and the fractal interface capacity CPE (insert Figure 9). The impedance of CPE capacity is given by the following equation [36] :…”
Section: Impedance Analysismentioning
confidence: 99%
“…One of these involves [Bi n I 4n ] nÀ anionic chains, but the structure has the space group Pbcn and is thus not isostructural with that of (6) (Buikin et al, 2018). Khelifi et al (2010) reported an unusual structure involving [H n Bi 2n Cl 11n ] nÀ anionic chains with hydrido bridges between Cl atoms within the repeat unit. Kulicka et al (2006) described polymorphs of salts involving 4-aminopyridinium and cis-double-chlorido-bridged [Bi n Cl 4n ] nÀ anionic zigzag chains at 100 and 250 K; the low-temperature form appears to be isostructural with that of (6).…”
Section: Figure 10mentioning
confidence: 99%